Variety Trial and Fertility of Fescue Cultivars in Southeast Kansas - Dale Helwig; Bruno Pedreira; Junior Yasuoka (Kansas Agricultural Experiment Station Research Reports, 2024)
In fall 2021, five varieties of fescue were planted at the K-State Research station outside of Columbus, Kansas. The varieties included two endophyte free (E-) varieties, two novel endophyte (NE) varieties, and one endophyte (E+) variety. The varieties were Atlas (E-), Cajun (E-), Bar Optima (NE), Estancia (NE), and K-31 (E+). Three rates of nitrogen were applied in the spring to each variety; 0, 50, and 100 units and each treatment was replicated three times. Due to the drought, measurements were not taken in 2022 but samples were obtained in 2023. The only stress the plots received was lack of moisture as the drought persisted in 2023. These plots were not grazed. Overall, addition of nitrogen increased biomass production in all cultivars evaluated. There was no difference in biomass produced in K-31 fescue between 50 or 100 units of nitrogen. Bar Optima had the greatest response to the additional nitrogen in regard to biomass production. However, as nitrogen increased, the crude protein increased for each variety. When biomass was measured in May, Cajun at both 50 and 100 units of nitrogen had the greatest yield, followed closely by yields with 100 units of nitrogen on Bar Optima and Estancia. Atlas and K-31 fescue varieties at both 50 and 100 units of nitrogen had similar biomass and had the lowest yields of the fertilized treatments. However, for total accumulation through the growing year, varieties fertilized with 100 units of N varieties out-yielded K-31. At 50 units of N the Bar Optima had the lowest total yield.
Keywords: fescue varieties; nitrogen; endophyte